Adoption of Improved Technologies Among Nagpur Mandarin Growers in Vidarbha - Anavrat , Vinod (Indian Journal of Extension Education, 2015)
Nagpur mandarin (Citrus reticulata Blanco) popularly known as 'Nagpur Orange' has got a Geographical Indication (GI)  tag identity. Besides the Vidarbha region of Maharashtra, it is grown in the three districts of Rajasthan and Madhya  Pradesh. Being a cash crop, mandarin cultivation in Maharashtra increased upto 1,35,000 ha and occupies top position in  terms of area. However, the average productivity of 9-10 tons/ha point at the dismal status of Nagpur mandarin industry  especially in Vidarbha. Hence, to ascertain the causes of technology non-adoption leading to low productivity, the study  was undertaken in the Nagpur mandarin growing area of Central India comprising 300 respondents in a stratified random  sampling. The study revealed that, growers with land large holdings were better adopters due to increased scientific  orientation and better extension contacts. Overall, the reason of non-adoption differed with the perceived importance of  technology by the respondents. However, lack of information was one of the major handicaps and the growers need to be  equipped with required information for accelerating the improved technology adoption process.
Keywords: Adoption; constraints; Nagpur mandarin